2006
DOI: 10.1038/sj.jp.7211561
|View full text |Cite
|
Sign up to set email alerts
|

Nasal continuous positive airway pressure from high flow cannula versus Infant Flow for preterm infants

Abstract: Objective: To compare the feasibility of continuous positive airway pressure (CPAP) support generated by high flow nasal cannula with conventional CPAP for prevention of reintubation among preterm infants with a birth weight of p1250 g.Study Design: Preterm infants were randomized to CPAP generated via high flow cannula or the Infant Flow Nasal CPAP System (VIASYS, Conshohocken, PA, USA) at extubation. Primary outcome was incidence of reintubation within 7 days. Secondary outcomes included change in oxygen use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(100 citation statements)
references
References 16 publications
1
92
0
7
Order By: Relevance
“…This would potentially explain the higher reintubation rate in infants randomized to HFNC in a recently published pilot study. 8 That study randomized 40 infants to HFNC or CPAP following Pharyngeal pressure with high-flow NC DJ Wilkinson et al extubation using flow rates according to the formula generated by Sreenan et al 3 The mean flow rate used was 1.6 l min À1 , which our study would predict delivered a pharyngeal pressure of only 2.5 cm H 2 O.…”
Section: Cannula Sizementioning
confidence: 96%
See 1 more Smart Citation
“…This would potentially explain the higher reintubation rate in infants randomized to HFNC in a recently published pilot study. 8 That study randomized 40 infants to HFNC or CPAP following Pharyngeal pressure with high-flow NC DJ Wilkinson et al extubation using flow rates according to the formula generated by Sreenan et al 3 The mean flow rate used was 1.6 l min À1 , which our study would predict delivered a pharyngeal pressure of only 2.5 cm H 2 O.…”
Section: Cannula Sizementioning
confidence: 96%
“…2,3 As a consequence of this, and because of its apparent ease of use and reduced nasal trauma, HFNC has gained considerable clinical support, 4 and has been used as an alternative to nasal continuous positive airway pressure (CPAP). [3][4][5][6][7][8][9] However to date, relatively little has been published on its efficacy or safety.…”
Section: Introductionmentioning
confidence: 99%
“…Several prospective randomized trials have compared HFNC versus CPAP for the respiratory management of preterm infants [89][90][91][92][93][94][95][96] ( In the 5 studies of primary support only, 3 compared the rate of respiratory failure, defined either by clinical worsening or the need for intubation, and revealed no differences. 91,93,95 Two additional studies did not assess respiratory failure, but compared pain and/or discomfort scores; an observational cross-sectional study in 60 preterm infants revealed that the application of HFNC was associated with less pain compared with nCPAP, 97 whereas a randomized crossover study in 20 preterm infants revealed no differences during treatment.…”
Section: Hfnc Versus Cpap For Noninvasive Respiratory Support Of Pretmentioning
confidence: 99%
“…15,16 Numerous studies have demonstrated the safety of HFNC in neonates, 17 but the amount of pressure actually provided by these devices remains in question. 18,19 In this issue of RESPIRATORY CARE, Volsko et al further elucidate the issue of continuous distending pressure generation by HFNC. 20 In their bench study, the nasal cannulae were optimally sized to models of premature, infant, and pediatric nares.…”
Section: See the Original Study On Page 1893mentioning
confidence: 99%
“…A randomized trial of nasal CPAP versus HFNC in preterm infants immediately following extubation found a significantly higher rate of re-intubation in the HFNC group. 18 Nair compared humidified HFNC to CPAP in preterm infants with RDS, within 6 hours of birth, and found similar rates of re-intubation and duration of respiratory support in the groups, but that study was terminated early due to the recall of the HFNC device utilized. 25 While these clinical investigations did not specifically record the amount of continuous distending pressure delivered by the HFNC devices, the inconsistent clinical benefit suggests that the continuous distending pressure was variable or inadequate.…”
Section: See the Original Study On Page 1893mentioning
confidence: 99%